Genetic Engineering of Crypthecodinium cohnii to Increase Growth and Lipid Accumulation - Diao, Jinjin; Song, Xinyu; Zhang, Xiaoqing; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2018)
In this study, we evaluated suitable selected markers and optimized transformation protocols to develop a new genetic transformation methodology for DHA-producing C. cohnii. Additionally, ribulose 1,5-bisphosphate carboxylase/oxygenase (RuBisCO), potentially involved in CO2 fixation under autotrophic conditions, was selected as the target for construction of a gene knockdown mutant. Our results show that the constructs were successfully inserted into the C. cohnii chromosome by homologous recombination. Comparative analysis showed that deletion of the RuBisCO gene promoted cell growth and increased the lipid content of C. cohnii under heterotrophic conditions compared with those of the wild-type. The liquid chromatography-mass spectrometry (LC-MS) based metabolomic analysis showed that the metabolites involved in energy metabolism were upregulated, suggesting that the deletion of the RuBisCO gene may contribute to the re-direction of more carbon or energy towards growth and lipid accumulation under heterotrophic conditions.